AKIBAT HUKUM TENGENBEWIJS TERHADAP AKTA OTENTIK DALAM HUKUM PEMBUKTIAN PADA PERKARA PERDATA - Ni Putu Riyani Kartika Sari (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2019)
As regulated on Article 164 HIR/ Article 284 RBg there are several kinds of evindence in civil cases such as written evidence, proof by witnesses, presumtions, confessions evidence, and oaths. One of the written evidence is authentic deed which was made by and before the authorized public officer at the place where the deed was made. The proof strength of authentic deed is perfect except declined and proven otherwise by the evidence of the opponent or tengenbewijs. Using notmative legal studies, this written is examining and discussing about the strength of the authentic deed and legal the strength of the authentic Regarding to the strength of an authentic deed on proofing process was of perfect proof which means what is written in the deed was really happened so that the judge must accept it and may not order the addition of proof anymore. But to the proof strength of the authentic deed can be defended by the evidence of opponent or tengenbewijs. The existence of evidence of the opponent against an authentic deed will invalidate the strength of perfect proof of an authentic deed because it will cause a lack on the authentic deed, so that in the process of proving the civil case, the authentic deed proof strength will be degraded to be an underhanded deed.